Impaired functioning of thermolabile methylenetetrahydrofolate reductase is dependent on riboflavin status: implications for riboflavin requirements - MCPARTLIN, JOSEPH; SCOTT, JOHN MARTIN (American Society for Clinical Nutrition, 2002)
Background: Methylenetetrahydrofolate reductase (MTHFR; EC 1.7.99.5) supplies the folate needed for the metabolism of homocysteine. A reduction in MTHFR activity, as occurs in the homozygous state for the 677CT (so-called thermolabile) enzyme variant (TT genotype), is associated with an increase in plasma total homocysteine (tHcy). Objective: In vitro studies suggest that the reduced activity of thermolabile MTHFR is due to the inappropriate loss of its riboflavin cofactor. We investigated the hypothesis that MTHFR activity in the TT genotype group is particularly sensitive to riboflavin status. Design: We studied tHcy and relevant B-vitamin status by MTHFR genotype in a cross-sectional study of 286 healthy subjects aged 19?63 y (median: 27 y). The effect of riboflavin status was examined by dividing the sample into tertiles of erythrocyte glutathionine reductase activation coefficient, a functional index of riboflavin status. Results: Lower red blood cell folate (P = 0.0001) and higher tHcy (P = 0.0082) concentrations were found in the TT group than in the heterozygous (CT) or wild-type (CC) groups. However, these expected relations in the total sample were driven by the TT group with the lowest riboflavin status, whose mean tHcy concentration (18.09 ?mol/L) was almost twice that of the CC or CT group. By contrast, adequate riboflavin status rendered the TT group neutral with respect to tHcy metabolism. Conclusions: The high tHcy concentration typically associated with homozygosity for the 677CT variant of MTHFR occurs only with poor riboflavin status. This may have important implications for governments considering new fortification policies aimed at the prevention of diseases for which this genotype is associated with increased risk.
PUBLISHED
Keywords: Homocysteine ? riboflavin ? methylenetetrahydrofolate reductase ? folate ? folic acid ? neural tube defects ? MTHFR genotype